Development of novel material systems for fiber-reinforced polymer applications - Ong, Priscilla Wah Min (2017)
Fibre Reinforced Polymers (FRPs) are widely used in Civil Engineering applications due to their high strength, toughness and lightweight properties. The Wet Lay-Up and Prepreg methods are commonly used in structural applications. However, they are arduous and time-consuming methods.